Pengaruh Model Pembelajaran Kooperatif Tipe Learning Together Terhadap Hasil Belajar Ekonomi Siswa Kelas XI SMA Negeri 3 Singaraja - Dewi, Ni Putu Puspita; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2024)
Students who used the Learning Together cooperative learning approach and students who used traditional learning methods were compared to see if there were any differences in economic learning outcomes. There were 94 XI IPS students in the study population. There were 63 students in the sample, 32 of whom were in the experimental group and 31 in the control group. The method of random sampling was used for the sampling. Pre- and post-test test procedures were used to collect data. The provided data were evaluated with the help of an independent sample t-test. The sig (2-tailed) value of 0.000-0.05 indicated that incorporating the Learning Together cooperative learning model into conventional teaching and learning practices had a significant impact on students' economics-related learning outcomes. The findings lead us to the conclusion that the Learning Together cooperative learning approach has the potential to enhance student learning outcomes.